(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The study of crimes is known as criminology. The field of criminology studies why people commit crimes. This is clearly connected to a variety of subjects, such as Criminal Justice, which examines Police Procedure in the context of maintaining societal control. Custody, prosecution, and the operation of the legal system are only a few of the criminology studies. Penology is the study of the prison system, including how prisons operate and how probation operates thereafter. Criminology does not attempt to determine how the world should be, but rather seeks to comprehend what it is. The essay discusses how a person’s envy and sex drive them to commit a crime. These offenses are sometimes committed without regard for the repercussions. Though this type of violence does not make national news, it fits into a trend that makes India a dangerous place. The article uses data from the National Crime Records Bureau (NCRB) to try to figure out how jealousy and sexual cravings are luring more people into its trap. The word "legal good" has the potential to reduce the number of crimes committed.